Peer Relationship Analysis and the Quality of Life at School in Early Adolescents - Lestari, Nur Eni; Safitri, Aisyah (Jurnal Pendidikan Keperawatan Indonesia, 2023)
The suboptimal state of quality of life will have an impact on the physical health and psychological welfare of individuals. When early adolescents are excluded from their age group, their quality of life is compromised. The primary objective of this research is to examine the correlation between peer relationships and the quality of life at school experienced by early adolescents. The  methodology employed in this study involved the utilization of a cross-sectional approach. The independent variables in this research encompass the following respondent characteristics: age, gender; peer relationships; and quality of life at school. The population under investigation consisted of 569 early adolescents in one of a state junior high school in South Jakarta. Total sampling was employed as the sampling technique for this study. The research instrument utilized was a modified questionnaire derived from The Peer Relationship Scale and The Quality of Life in School Questionnaire, which underwent rigorous testing to ensure its validity and reliability. In conducting bivariate analysis, the chi-square test was employed. The findings of this research indicate that a majority of the adolescents surveyed exhibited poor peer relationships, with 312 respondents (54.8%) falling into this category. Furthermore, a significant proportion of the respondents reported a low quality of life at school, with 378 adolescents (66.4%) falling into this category. In addition, the majority of the sub-dimensions of quality of life in school, namely psychosocial well-being, attitudes towards school, student-teacher relationships, and the school environment, were reported as being poor (64.1%, 80.3%, 64.7%, and 56.4%, respectively). The quality of relationships between peers impacts adolescents' quality of life at school (p value = 0.000; α 0.05). Positive peer relationships have the potential to enhance the emotional and psychological well-being of adolescents, whereas extended conflict can engender the contrary effect.